Hemoglobina, hierro sérico y ferritina como indicadores de anemia en infantes menores de dos años en el cantón Alausí, Chimborazo. - Quishpi Lema, Heidy Rubí (2025)
Anemia is the most common disease in children, defined as a public health problem; 43% represent the 280 million children worldwide who suffer from this pathology. The main effects on child development are observed in infants aged 6 to 24 months, in whom there may be consequences in growth, cognitive performance, decreased physical abilities, and deterioration of immune defenses. The main objective was to assess hemoglobin, serum iron, and ferritin as indicators of anemia in infants under two years of age in the canton Alausí, Chimborazo. A relational, non-experimental field methodology of a prospective, cross-sectional type with a quantitative design was used. The study population included 200 infants, of whom 58 children made up the sample met the inclusion and exclusion criteria. This research on the assessment of hemoglobin, iron, and ferritin showed that 20.68% present iron deficiency anemia, being more prevalent in the 0-12 months age group with 13.79%. Regarding hematological and biochemical tests, it was evidenced the three parameters show a relationship for diagnosing this pathology. Finally, it was found that there is a prevalence of 20.69% of iron deficiency anemia in the studied population.